Vitamins improve the effect of heavy metal exposure in arthritis after hysterectomy - Xu, Binkai; Wu, Xian; Liu, Zhiwei; Yu, Bin (Frontiers in Nutrition, 2025)
BackgroundThe interplay between gynaecological surgeries and arthritis pathogenesis remains poorly understood. This study offers new insights into potential health risks associated with post-hysterectomy.MethodsThe cross-sectional study utilized data from the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2018, which cannot establish the causation. The effects of five serum heavy metal and nine vitamin intakes were evaluated.ResultsA total of 3,121 participants with complete data from NHANES (2007 ~ 2018) were included in this study. The prevalence of arthritis among participants having undergone hysterectomy was significantly increased (58.25% vs. 31.64%, p < 0.001). Meanwhile, the levels of blood lead were significantly increased in women having undergone gynaecological surgery (p < 0.001) and women with arthritis (p < 0.001). After additionally adjusting, hysterectomy was still associated with an increased risk of arthritis (OR = 3.33, p < 0.0001). A non-linear (L-shaped) relationship was observed in blood lead, mercury, and cadmium (p for non-linearity <0.001). Blood lead was the highest weighted quantile sum (WQS) weigh among five heavy metals, with the highest contributions of 0.72. Mediation analysis demonstrated that blood lead accounted for 6.02% of the observed association between hysterectomy and arthritis (p < 0.001). The RCS curves confirmed that there was a non-linear (L-shaped) relationship between vitamin K, vitamin D, and the risk of arthritis caused by hysterectomy (p < 0.001).ConclusionHysterectomy is associated with an increased risk of arthritis, with a focus on blood lead as a mediating factor and vitamin intake as a potential protective factor. It will contribute to the long-term health management after hysterectomy.